Antimalarial and antimycobacterial agents from Streptomyces sp. BCC27095. Issue 49 (9th December 2015) - Intaraudom, Chakapong; Bunbamrung, Nantiya; Dramae, Aibrohim; Danwisetkanjana, Kannawat; Rachtawee, Pranee; Pittayakhajonwut, Pattama
Graphical abstract: Abstract: Investigation of the terrestrial Streptomyces sp. BCC27095 led to the isolation of two new (1 and2 ) and two known (3 and5 ) anthraquinone derivatives along with the previously reported compound, steffimycin B (4 ). The chemical structures were determined on the basis of NMR spectroscopic data. These compounds exhibited significant antimalarial (against Plasmodium falciparum, K-1 multidrug resistant strain) and antimycobacterial (against Mycobacterium tuberculosis H37Ra) activities with IC50 values in the range of 0.32–3.20 μg/mL and MIC in a range of 0.0031–1.56 μg/mL, respectively. They were also evaluated for antibacterial activity against Bacillus cereus and for cytotoxicity against both malignant (MCF-7, KB, NCI-H187) and non-malignant (Vero) cells.